Are Capital Goods Tariffs Different? - Meleshchuk, Sergii (IMF Working Papers; Working Paper ;, 2020)
In this paper we demonstrate the importance of distinguishing capital goods tariffs from other tariffs. Using exposure to a quasi-natural experiment induced by a trade reform in Colombia, we find that firms that have been more exposed to a reduction in intermediate and consumption input or output tariffs do not significantly increase their investment rates. However, firms' investment rate increase strongly in response to a reduction in capital goods input tariffs. Firms do not substitute capital with labor, but instead also increase employment, especially for production workers. Reduction in other tariff rates do not increase investment and employment. Our results suggest that a reduction in the relative price of capital goods can significantly boost investment and employment and does not seem to lead to a decline in the labor share.